Optimal bat orientation and ball-impact point for maximization of batted ball velocity in opposite field hitting - Shimura, M.; Miyazawa, T.; Yanai, T. (Japan Journal of Physical Education, Health and Sport Sciences, 2018)
The purpose of this study was to determine the impact conditions that enable a batter to hit a pitched ball toward the opposite field. Three-dimensional finite element analysis was used to construct a model for the impact between a baseball and a wooden baseball bat, and a series of simulations were conducted with various bat angles and under-cut distances. The bat angle at ball impact was set in a horizontal range from -31 to 20° and a vertical range from 0 to 51° with a 3° interval. The under-cut distance was altered by changing the vertical angle of the line of impact in a range from 0 to 30° with a 5° interval. The velocity and angle of projection of the batted ball were determined for each simulated condition. The simulation model was validated by comparing the simulation outcome with the corresponding experimental data obtained from opposite-field hitting practice performed by collegiate baseball players. The results showed that when a batter intends to hit a ball toward a given horizontal angle in the opposite field with the highest speed, the batter should impact the ball with the bat facing about 60% of the horizontal angle toward which to launch the ball and with the line of impact angled upward at 5~10° from the horizontal plane. In addition, the horizontal angle of the batted ball and the velocity of the batted ball were found to change systematically when the vertical angle of the line of impact and the vertical bat angle were altered: For a given horizontal angle toward which to launch the batted ball, there was a trade-off relationship between the vertical angle of the line of impact and the vertical bat angle.